A CASE OF NEUROGENIC FORM OF WILSON'S DISEASE – A RARE DISORDER IN COPPER TRANSPORT. - VASANTHAN.M.; KALAISELVI.V.S. (International Journal of Pharma and Bio Sciences, 2013)
Among the various disorders of metabolism existing in nature, there are certain disorders whose prognosis is good and which are treatable to some extent. The early diagnosis and treatment helps in modifying the changes caused by the diseases. The failure for early diagnosis and intervention is quiet common among people in the developing countries. This case report is an example for such negligence. The patient here presents with advanced symptoms at an elderly age and was diagnosed as Wilson’s disease.